ANALISIS KRIMINOLOGI KEJAHATAN PENGGELAPAN DAN PENIPUAN DANA UMROH OLEH BIRO PENYELENGGARA PERJALANAN IBADAH UMROH PT.NABILA TRAVEL DI KOTA MEDAN - Enjang Bahri (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
The rise of fraudulent umrah funds by companies that organize Umrah trips is inseparable from the role of the government as the party that gives business permits and is the party responsible for supervising the conduct of business activities carried out by the Bureau of Organizing Umrah Worship Travels.Based on the results of the study, it was found that the regulation of fraud and embezzlement of prospective Umrah pilgrims in Indonesian legislation, there are at least three relevant laws, namely Law No. 1 of 1956 concerning the Criminal Code, Law No. 8 of 1999 concerning Consumer Protection and Law No. 13 of 2008 concerning the Implementation of Hajj and Umrah services. The cause of the fraud and fraud of Umrah funds by PT. Nabila Putra Mandiri is an encouragement in the suspect to fulfill unlimited desires (lusts) and a culture of people who are trustworthy and tempted by lure that is profitable. The government policy prevented the embezzlement of pilgrimage pilgrimage funds by the umroh travel organizer bureau, namely by making a new policy in the system of Hajj and Umrah administration through the Integrated Umrah Supervision Information System and Special Hajj which was based on electronics.Keywords: Criminology analysis, embezzlement, Fund Umrah.